Credit facilities as an indicator of performance Short-term investments in commercial banks An Empirical Study on the branches of the Rafidain Bank in the province of Nineveh For the period 2003-2007 - عدنان سالم قاسم (Iraqi Journal for Administrative Sciences, 2024)
Bank’s activity is considered an important evidence on economic and Financial development, credit facilities-both direct and indirect-is one of the services that it present to a great number of traders and industrialists to enhance their economic activity through the year which, in return, participate in the economic growth by using apart of money in a short-term investment, the research which had applied on sectors of Al-Rafidain bank in Neineva province proved that there is a decrease in provided money asing in the credit facilities (overdraft, bills discount, letters of guarantee, short-term loans, documentary credit. The research reached important recommendations that are returning confidence between banks and costumers and producing modern and development products in order to compete private banks.